Muscle-Restricted Nicotinamide Adenine Dinucleotide Phosphate Oxidase 4 Knockout Partially Corrects Muscle Contractility After Spinal Cord Injury in Mice - Carlos A. Toro; Rita De Gasperi; Abdurrahman Aslan; Nicholas Johnson; Mustafa M. Siddiq; Christine Chow; Wei Zhao; Lauren Harlow; Zachary Graham; Xin-Hua Liu; Junichi Sadoshima; Ravi Iyengar; et al. (Neurotrauma Reports, 2024)
Spinal cord injury (SCI) results in severe atrophy of skeletal muscle in paralyzed regions, and a decrease in the force generated by muscle per unit of cross-sectional area. Oxidation of skeletal muscle ryanodine 1 receptors (RyR1) reduces contractile force as a result of reduced binding of calstabin 1 to RyR1. One cause of RyR1 oxidation is nicotinamide adenine dinucleotide phosphate (NADPH) oxidase 4 (Nox4). We have previously shown that, in rats, RyR1 was oxidized and bound less to calstabin 1 at 56 days after SCI by spinal cord transection. Here, we used a conditional knockout (KO) mouse model of Nox4 in skeletal muscle to investigate the role of Nox4 in reduced muscle specific force after SCI. Peak twitch force of extensor digitorum longus muscles in control mice after SCI was reduced by 42% compared with sham-operated controls, but was increased by ∼43% in SCI Nox4 conditional KO mice compared with SCI controls, although it remained less than that for sham-operated controls. Unlike what was previously observed in rats after SCI, the expression of Nox4 was not increased in gastrocnemius muscle, and binding of calstabin 1 to RyR1 was not reduced in this muscle. The results suggest that Nox4 is directly involved in reduction in muscle twitch force after SCI, although further studies are needed to understand the mechanistic basis for this linkage.